How urban development affects green development efficiency in China: Taking the city cluster of Yangtze river economic belt as an example - Huang, Jing; Shangguan, Ziheng; Gui, Tiantian; Liu, Jianping (Frontiers in Environmental Science, 2023)
Introduction: In order to change the long-term economic development model which is at the expense of the environment, China proposed a series of new energy development and environmental intervention policies. However, there is no evidence to support the impact of urban development on the green development efficiency (GDE) under China’s macroeconomic policies at present. In order to answer this research question and help the government to improve the GDE, this study takes the Yangtze River Economic Belt (YREB) city cluster (41 cities) in China as an example to conduct an empirical study. Methods: We first measure the GDE of these cities by Slack Based Model (SBM). Then, the Tobit model is used to measure the impact of urban development elements, namely population urbanization, land urbanization, and urban industrial development, on GDE. Results and Discussion: The analysis of the data leads to the following conclusions and suggestions: 1) The GDE of the city cluster in the YREB has generally been improved driven by policies. But compared to policy interventions, the level of science, technology and management are the primary drivers of long-term improvement in GDE. 2) In order to avoid the economic development and environmental capacity failure to afford the increase in energy consumption and pollution discharge caused by population urbanization and land urbanization, local governments need to promote energy transformation, increase environmental protection efforts and attract top-tier talent. 3) The improvement of GDE by industrial upgrading is a dynamic and slow process, and blindly pushing industrial restructuring will lead to a decline in GDE. Therefore, the Chinese government needs to provide an ecologically suitable environment for local industrial development, which needs to avoid “pulling out the seedlings” and “one-size-fits-all” approach.